Sodyum metaboratın protein temelli yangın köpüklerinde hidroliz vasıtası olarak kullanılması - Akova, Aylin (Fen Bilimleri Enstitüsü, 1995)
Protein türü yangın söndürme köpüğü protein içeren maddelerin alkali ortamda hidrolizlenmesiyle üretilir. Hidrolizat nötralize edilir ve gerekli yoğunluğa kadar buharlaştırılır. Ürüne kararlı bir köpük elde etmek ve depolama mukavemeti kazandırmak için katkılar yapılır. Geliştirilen yeni yöntemde, keratin içeren boynuz sodyum metaborat ile hidrolizlenmiş ve borik asit ile nötralize edilmiştir. Sodyum metaboratın sahip olduğu antisepik özellik ve yanmazlık özellikleri nedeniyle ayrıca katkı maddesi katılmamıştır. Yapılan fiziksel özellik belirme ve söndürme testlerinden üretilen köpüğün özellikle akaryakıt yangınlarında etkili olduğu sonucuna varılmıştır.

Fire fighting foam is a mass of bubbles farmed by various methods from aqueous solutions of especially for mulated foaming agents. Since foam is lighter than flammehle liquids, it floats on all flammable or combus tible liquids, producing an air excluding, cooling con- tininuous layer of vapor-sealing Water bearing material or purposes of halting or preventing combustion. Fire fighting foams are formulated in several ways for fire extinguishing action. Some foams are thick and viscous forming heat resistant blankets over burning liquid surfaces and vertical areas. In general, foam is used especially when a very light cohesive blanketing and cooling fire controlling or extinguishing agent is needed. Special types of foams are required for special situations such as cavity filling and- water miscible solvent fire protection. Various types of fire fighting foams that are available and used for different fires, are protein foaming agents, aqueous film-forming foaming agents, synthetic hydrocarbon surfactant foaming agents alcohol type foaming agents, and high expansion foaming agents. Protein type air foams utilize aqueous liquid con centrates proportioned with water for bubble generation. These concentrates contain high molecular weight natural proteinaceous polymers derived from chemical hydrolysis of natural protein solids. The polymers give elasticity, mechanical strength and Water retention capability to the foam generated. The concentrates also contain dissolved polyvalent metalic salts, which aid the protein polymers in their bubble strengthening capability when the foam is exposed to the heat and flame. Vll Drganic solvents are added to concentrates to improve their foamability and foam uniformity as well as ta control their viscosity at lowered temperatures. Protein type concentrates are available for proportioning to a final concentration of either 3 or 6 percent by volume using either fresh water or sea water. In general these concentrates produce dense, viscous foams of high stability, high heat resistance, and better resistance to burnback than many other foaming agents. They are nontoxic and biodegreable after dilution. Fluoroprotein foams are similar in composition to protein foam concentrates, but in addition to protein polymers, they contain fluorinated surface active agent that confer a "fuel shedding" property to the foam generated. This makes them particularly effective for fire fighthing conditions where the foam becomes coated with fuel, such as in the method of subsurface injection of foam for tank fire fighting and nozzle ormonitor foam applications where the foam may often be plunged into the fuel. Fluoroprotein foams are more effective for in depth petroleum or hydrocarbon fuel fi£es than other agents because of this property of "fuel shedding". In addition, these foams demonstrate better compahdlity with dry chemical agents than do the protein type foams. They also posses superior vapor securing and burnback resistance characteristics. Fluoroprotein type concentrates are available for proportioning to a final concentrates of either fresh water or sea water. Fire fighting foams are useful on surfaces when the cooling effect of water is nedded and when continuous film-coating characteristics of a light, opaque form of water, capable of sealing vapors, are nedded. The most important use of foams is in fighting fires in flammable or combustible liquids. Foam is the only permanent extinguishing agent used for fires of this type. Its application allows fire fighters to extinguish fires Progressively. A foam blanket covering a liquid surface is capable of preventing vapor transmission for sometime, depending an its stability and depth. Fuel spills are quickly rendered safe by foam blanketing. The blanket may be removed after a suitable period of time; often it has no detrimental effect on the product with which it comes into cantect. VI 11 Foams may be used to disminish or halt the generation of flammable vapors from nonburning liquids or solids. They may be used to fill cavities or enclosures where toxic or flammable gases may collect. To produce foam concentrates horn, hoof, feather which consist of protein is hydrolyzed with Ga(0H)" or NaOH. Hydrolyzate is neutralized with AcDH, sulfonic acid, Hcl, Then the neutralized hydrolyzate is mixed with FeSQ,, CaClp, urea as stabilizer and phenol as antiseptic. In this study horn was hydrolyzed with both NaOH and NaBD". Protein and aminoacid content of the hydrolyzate was Determined. Protein content of the horn and hydrolyzate was determined with Kjeldahl method and aminoacid content was determined by aminoacid analyzer. The applied test for determining the protein and the aminoacid contents of the horn and NaDH, NaBD" hydrolyzates are given in Table 1. Comparison of the aminoacid content of the NaDH and NaBD" hydrolyzates shows that carrying out hydrolyzing process with NaDH destroys arginine, cystine, isoleucine and threonine. The NaBD" hydrolyzate was tested as foam fire extinguisher after neutralized with boric acid. There was no need to any foam stabilizer and antiseptic agent, The physical properties of NaB0" hydrolyzate are shown in Table 2. The extinguishing properties of NaBG_ hydrolyzate and the foam which contain surfactant are given in Table 3. IX TABLE: 1. Protein- and Aminoacid Contents of the Horn and, NaOH, NaB0" Hydrolyzates TABLE.-2. Physical Properties of NaBO Hydrolyzate These results show that the foam containing surfactant has high extinguishing capability, heat resis tance, and foam thickness.
Use of sodium metaborate as hydrolyzing agent for the preparation of protein based fire fighting foam
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1995
Keywords: Hidroliz; Köpük; Yangın söndürme ekipleri; Hydrolysis; Foam; Fire extinguishing teams